2018
DOI: 10.1002/jcop.21978
|View full text |Cite
|
Sign up to set email alerts
|

Bully victimization, depression, and the role of protective factors among college LGBTQ students

Abstract: This study surveyed 347 lesbian, gay, bisexual, transgender, and questioning college students from across the United States concerning their bully victimization, depressive symptoms, and sources of support. Participants responded to an online survey that asked them about their victimization experiences during the 3 months prior to the survey. The results indicate that four types of bully victimization (verbal, relational, cyber, and physical) occur during the college years, and that victimization relates posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…Studies have begun to highlight the fact that despite initial challenges, not all victims of bullying develop mental health problems (Baker & Bugay, 2011), prompting researchers to investigate potential protective factors that could alleviate the negative effects of bullying involvement on emotional difficulties. Previous studies have demonstrated the role of peer, school, and family support (Moran, Chen, & Tryon, 2018), but little research has explored the role of individual psychological mechanisms in response to bullying involvement (Cassidy, McLaughlin, & McDowell, 2014). Given the current reality that victimization appears inevitable for some children (Egan & Todorov, 2009), counselors should have a better understanding of the underlying mechanism of how individual protective factors could mitigate the negative influences of bullying involvement.…”
Section: Victimization and Emotional Difficultiesmentioning
confidence: 94%
“…Studies have begun to highlight the fact that despite initial challenges, not all victims of bullying develop mental health problems (Baker & Bugay, 2011), prompting researchers to investigate potential protective factors that could alleviate the negative effects of bullying involvement on emotional difficulties. Previous studies have demonstrated the role of peer, school, and family support (Moran, Chen, & Tryon, 2018), but little research has explored the role of individual psychological mechanisms in response to bullying involvement (Cassidy, McLaughlin, & McDowell, 2014). Given the current reality that victimization appears inevitable for some children (Egan & Todorov, 2009), counselors should have a better understanding of the underlying mechanism of how individual protective factors could mitigate the negative influences of bullying involvement.…”
Section: Victimization and Emotional Difficultiesmentioning
confidence: 94%
“…Due to the diversity of sexual and gender identities (e.g., lesbian, gay, bisexual, queer, questioning, pansexual, fluid) among our SGM graduate students and the small number of participants in each identity subgroup, we were unable to conduct meaningful statistical analysis to examine whether subgroup membership affects SGM students' experiences in school psychology graduate programs. Future research should consider examining the role of subgroup membership in LGBTQ students' experiences in school psychology programs, because research has suggested that members of sexual and gender minorities may experience challenges that are unique to their subgroup identities (e.g., Moran et al, 2018). We acknowledge that there was no transgender participant in our SGM sample.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…We defined bullying victimization experiences as being the victim of physical or verbal attacks, being excluded from activities, or spreading rumors, with any of these experiences occurring either online or in person (Moran, Chen, & Tryon, 2018).…”
Section: Participantsmentioning
confidence: 99%